African Sociological Review / Revue Africaine de Sociologie (JSTOR)
The African Sociological Review is a bi-annual publication of CODESRIA, Dakar, Senegal. It welcomes articles and other academic communications from scholars in Africa and elsewhere regarding issues of African and general social analysis. The Review exists in the first instance to promote the extension of sociological and anthropological thought among scholars working in Africa. Relevant work from elsewhere will however also be considered. Contributions may be in English or French.
Keywords: African Studies